Khataman Qur’an Pra-Acara Alako Gebhai Desa Grujugan, Sumenep, Media Untuk Menangkal Bala’ Dan Memperoleh Berkah - Wedi, Agus (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
This paper to dercribe the practice of khataman Qur'an in the Pra-Acara Alako Gabhai tradition practiced by Grujugan, Sumenep, Madura island society ethnographically, in order to find its meaning. Based on the interpretation (Externalization, Objectification, and Internalisation) of cultures theory found out that interpreted the Grujugan society recognizes the concepts that are based on the religious basis, which has ultimate meaning as a way to get the salvation and blessings. These concepts were then believe as the true and real, which then formulated into various syimbols in the Grujugan tradition. These symbols have the full meaning that returns to those concepts and suggested living traditions or action tradition, which is delivered persuasively by Kyai. Through those concepts people were then motivated to perform khataman Qur'an in the Pra-Acara Alako Gabhai tradition. The practice of this tradition was able to create reseption and moods of a person, which then reflected into the daily life, felt as if to justify the existing concepts, so that the feeling is uniquely realistic